KAJIAN SPASIAL RUANG PUBLIK (PUBLIC SPACE) UNTUK AKTIVITAS BERMAIN DI KAWASAN KAMPUNG RAMAH ANAK GOLO, KOTA YOGYAKARTA - , DINA AGUSTINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Public space functions as a place for community activities ranging from interact, communicate, socialize, and play for children. However, quick development in the city resulted in reducing availability of public spaces, particularly public space as a place to play. This limitation makes children in the village area of town utilize the inapropriate space to fulfill their needs to play. Based on the existence of above problems, the study is aimed: 1) To measure the criteria of public space used for play activities in Golo Child Friendly Village, 2) To measure the play behavior of children in the public space in Golo Child Friendly Village, 3) Analyze the spatial existence of public space for play activities in Golo Child Friendly Village. The data collection technique was done through direct observation and indepth interview. Interviews were conducted to children of primary school age (6-12 years) and to key persons by using accidental sampling technique. The unit of analysis in this study was the location of used public space for play activities. Data analysis that used in this research was descriptive qualitative analysis. The results of this study indicate that most of used public space for play activities do not meet the criteria which is considered appropriate space for children playground. Dynamic children's play activities in the public space also resulted in spatial phenomena ranging from pattern of space, structure of space, process of space, organization of space, tendency of space, interaction of space, and association of space.